Peanut Variety Performance in Florida, 2006–2009 - Barry L. Tillman; Mark W. Gomillion; Justin McKinney; George Person; Bill D. Thomas (EDIS)
SS-AGR-330, a 10-page illustrated report by B.L. Tillman, M.W. Gomillion, J. McKinney, G. Person, and W.D. Thomas, provides data from University of Florida peanut trials conducted in Florida at IFAS research centers located in Gainesville (Citra), Marianna, and Jay from 2006–2009. Published by the UF Department of Agronomy, March 2010.